2014
DOI: 10.1038/eye.2013.229
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and vitreous fluid levels of Dickkopf-1 in patients with diabetic retinopathy

Abstract: Purpose Dickkopf-1 (DKK-1) is a secreted inhibitor of the Wnt/b-catenin signaling pathway, which plays a pathogenic role in diabetic retinopathy (DR). We aimed to investigate whether DKK-1 levels in the plasma and the vitreous are associated with DR in type 2 diabetes mellitus (DM) patients. Methods Case-control study: plasma samples were collected from 125 type 2 DM including 81 DR (29 non-proliferative DR (NPDR) and 52 proliferative DR (PDR)), 44 non-DR patients (NDR), and 100 non-diabetic controls. Undilute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…Table 3 summarizes the treatment options for clinical management of DR complications. [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] Table 4 also depicts the data of a study in an animal model where some pertinent particles believed to improve oxidative stress as well as prevent or delay DR development. [65][66][67][68][69][70][71][72][73][74][75] It is a proven fact that oxidative stress enhances the progression of DR hence, decreasing the degree of such stress has been observed in clinical situations to contra arrest DR pathological problems.…”
Section: Vitrectomymentioning
confidence: 99%
“…Table 3 summarizes the treatment options for clinical management of DR complications. [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] Table 4 also depicts the data of a study in an animal model where some pertinent particles believed to improve oxidative stress as well as prevent or delay DR development. [65][66][67][68][69][70][71][72][73][74][75] It is a proven fact that oxidative stress enhances the progression of DR hence, decreasing the degree of such stress has been observed in clinical situations to contra arrest DR pathological problems.…”
Section: Vitrectomymentioning
confidence: 99%
“…It has been reported that the protein expression level of DKK1 is significantly increased in the serum of patients with rheumatoid arthritis (6), and DKK1 regulates bone development and accrual and maintenance of bone mass (7,8). Recently, a study showed that plasma DKK-1 levels were significantly lower in DR patients compared with non-diabetic controls and non-DR (NDR) patients (9). Furthermore, DKK-1 levels were lower in proliferative DR (PDR) patients compared with non-proliferative PDR (NPDR) patients (9).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study showed that plasma DKK-1 levels were significantly lower in DR patients compared with non-diabetic controls and non-DR (NDR) patients (9). Furthermore, DKK-1 levels were lower in proliferative DR (PDR) patients compared with non-proliferative PDR (NPDR) patients (9). However, there is no information regarding the effects of DKK1 in RPE cells.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of DKK-1 and of the bone-protective marker OPG protein level were comparable to the reference range (18,19) at T0 and, showed non-significant oscillations in the subsequent follow-up points. A specular pattern of was observed between the oscillating expression of these two biomarkers at all time points.…”
Section: Evaluation Of Serum Protein Levels (T0 T1 T2 T4) (Table 4mentioning
confidence: 52%